Correlation Between Consumption Patterns and Knowledge with Incident of Anemia on Teenagers in State Junior Hight School Tigo Lurah, Solok Recency - Asy Syifa, Rahma; Hasniyati, Rina; Ismanilda (proceedinginternational, 2024)
One of the health problems that often occurs in teenagers, especially teenager girls, is anemia. Anemia is a condition where the number of red blood cells or haemoglobin (Hb) of a person is less than normal. Anemia is one of the common blood disorders that occurs when the level of blood cells (erythrocytes) in the blood is too low. The data from Riskesdas in 2018 showed that the prevalence of anemia among teenage girls aged 13-18 years in West Sumatra was 26.4%, exceeding the national average prevalence of anemia of 21.7%. Some areas in Solok Regency are remote areas, one of which is Tigo Lurah District. Sekolah Menengah Pertama Negeri (SMPN) 1 Tigo Lurah, precisely located in Batu Bajanjang village, is a school located in a remote area and needs attention in health services. This research aims to determine the correlation between consumption patterns and knowledge with the incidence of anemia in teenage girls at SMPN 1 Tigo Lurah, Solok Regency. This research is an observational study with a cross-sectional design with a Purposive Sampling technique. Data collection was divided into primary and secondary data. Primary data includes consumption patterns, nutritional knowledge, and health status (Hemoglobin Level) of female students. The results of the research can be concluded that more than one-third (36.7%) of girl teenage girls suffer from anemia, 73.5% of teenage girls’ nutritional knowledge level is less, a high proportion of teenage girls who have less energy consumption 38.8% and less protein is 67.3%. It can be concluded that there is a significant correlation between energy and protein consumption and the incidence of anemia.